2010
DOI: 10.1074/jbc.m109.091108
|View full text |Cite
|
Sign up to set email alerts
|

NMR Analysis of the Structure, Dynamics, and Unique Oligomerization Properties of the Chemokine CCL27

Abstract: Chemokines have two essential interactions in vivo, with G protein-coupled receptors, which activate intracellular signaling pathways, and with glycosaminoglycans (GAGs), which are involved in cell surface localization and transport. Although it has been shown that chemokines bind and activate their respective G protein-coupled receptors as monomers, many chemokines oligomerize upon GAG binding, and the ability to oligomerize and bind GAGs is required for in vivo function. In this study, we investigated the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 65 publications
3
48
0
Order By: Relevance
“…To investigate further the monomer-dimer properties of NAP-2 and TC-1, NMR diffusion studies were conducted using the internal standard dioxane, as has been done for other chemokines (9,20,51). For these experiments, the concentrations and conditions of the chemokine samples were carefully maintained to be consistent with each other for direct comparison, and a dilute protein concentration of 0.1 mM was used to obtain a more observable difference in the dimerization properties of the chemokines.…”
Section: Resultsmentioning
confidence: 99%
“…To investigate further the monomer-dimer properties of NAP-2 and TC-1, NMR diffusion studies were conducted using the internal standard dioxane, as has been done for other chemokines (9,20,51). For these experiments, the concentrations and conditions of the chemokine samples were carefully maintained to be consistent with each other for direct comparison, and a dilute protein concentration of 0.1 mM was used to obtain a more observable difference in the dimerization properties of the chemokines.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that the CXCL8 dimer is the high-affinity GAG ligand (26) and that, for various CC chemokines, GAG binding and dimerization/oligomerization are coupled (45,46). Chemokine expression in vivo is complex, and both robust expression of multiple chemokines and selective expression of just one chemokine have been observed, depending upon the biological context.…”
Section: Discussionmentioning
confidence: 99%
“…Two x-ray structures of chemokine-disaccharide are known, and most NMR structural studies also report only disaccharide binding, which provides only limited insights (46,47). However, NMR studies have had better success with longer GAGs, but the extent of the structural insights varies among different chemokines and seems to be critically dependent on experimental conditions (21,31,48). Recent studies by Handel and co-workers (21) on CCL27 and Volkman and co-workers (31) on CXCL12 using different oligosaccharides, protein concentrations, protein:GAG ratios, and variants (monomer and dimer) have shown that chemokine structural plasticity, oligomerization properties, GAG length, and binding-induced oligomerization/aggregation/precipitation are intimately coupled.…”
Section: Discussionmentioning
confidence: 99%